Gender Disparities in Physician Assistant Educator Promotion and Compensation: A Mixed Methods Approach. Issue 1 (23rd March 2023) - Loder, Rayne; Coombs, Jennifer; Najmabadi, Shahpar; Henry, Trenton; Ryujin, Darin; Valentin, Virginia
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: The gender wage gap is well documented in many industries. A disparity in salary between female and male physician assistant (PA) educators has been demonstrated, but disparities in academic rank have not been shown. The purpose of this study was to re-examine gender disparities in compensation to PA educators and to explore whether gender-based disparities exist in promotion to higher academic rank in this field. Methods: An explanatory sequential mixed-methods design was used to determine differences in salary and rank by gender. PA Education Association Faculty and Directors Survey data from 2014, 2017, and 2019 were analyzed. A focus group was conducted to explain the findings and understand the barriers to promotion for female faculty. Results: Female PA faculty members earn $7573 less than their male colleagues when controlling for all other variables. Female faculty members have an increased likelihood (RR 1.150) for being in early career stage versus late career stage. Obtaining a doctoral degree decreased the risk for being in an early career stage (RR 0.567) with men twice as likely to have a doctoral degree as women. Discussion: Rank and salary disparities exist in PA faculty by gender. Female faculty are less likely to hold doctoral degrees or to be promoted to higher academic ranks, and they earn less than men. Degree level and career track are themes unique to the PA education profession, and further research is needed to understand their impact. With more women entering PA education, pay equity and promotion need to be addressed.